How different cardioplegic solutions influence genes expression and cytokine response in an immature rat heart model of ischemia/reperfusion? - Arslan Mamedov; Dovydas Gečys; Povilas Jakuška; Rimantas Treinys; Deimantė Narauskaitė; Serik Aitaliyev; Eglė Rumbinaitė; Dainius Karčiauskas; Rimantas Benetis; Edgaras Stankevičius (PLoS ONE, 2025)
Introduction The use of cardioplegia not only achieves cardiac arrest but also minimizes ischemic/reperfusion (I/R) injury, potentially improving short- or long-term outcomes. The aim of this study was to evaluate the impact of different cardioplegic solutions – del Nido, Custodiol HTK and St. Thomas on genes expression and cytokines response in an immature rat heart model of I/R using the Langendorff preparation. Expression of genes which are involved in cell cycle, proliferation, apoptosis resistance and response to hypoxia were determined in cardiac tissue, as well as levels pro/anti-inflammatory cytokines were measured. Methods A total of 39 male Wistar albino rats were utilized in this study. Experimental animals were divided into 3 groups, four animals in each following groups: St. Thomas (ST), Custodiol HTK (HTK) and del Nido (DN) group. Moreover, each of these groups was divided into 3 groups according to ischemia’s time: 1h ischemia with 20 min reperfusion time, 2h ischemia with 40 min reperfusion time, 4h ischemia with 80 min reperfusion and control groups (K-PRF) with 30 minutes of perfusion was performed in the K-PRF (n = 3). The heart was removed from the chest and immediately frozen at –81°C. Results All cardioplegic solutions effectively modulate the expression of HIF1A, FOS, and BNIP2 genes. The results indicated that DN actively induces HIF1A within the first hour. Compared to the ST, and HTK groups, the expression of the HIF1A gene was on average 2 times higher (P < 0.01). Similar results were observed in the 2-hour group. After 4 hours, the effect of cardioplegic solutions continued to maintain the dynamics, but the differences were not statistically significant. The expression of the FOS gene after 2 and 4 hours of incubation with the DN solution remained significantly higher compared to ST (P < 0.05) and HTK (P < 0.05). A comparative analysis with the perfusion group showed that BNIP2 gene expression in the ST and HTK solution groups was significantly lower than in perfused tissue (P < 0.05). Pro-inflammatory cytokines: TNF-alpha, IL-6 and anti-inflammatory cytokines: IL-4 and IL-10 were evaluated. The results showed that there was no statistically significant difference between the groups (P > 0.05). Conclusion In our experiment, statistically significant differences were not observed in cytokines. Although statistically significant differences were observed only in gene expression, and only in the rat model, the overall results suggest that del Nido cardioplegic solution may provide better cellular protection. It is also worth mentioning that gene expression and cytokines change are not direct markers of cardioprotection. Further research is needed to confirm these results in human tissues and broader clinical settings.